Increased Expression of Laminin Subunit Alpha 1 Chain by dCas9-VP160 - Arnaud Perrin; Joël Rousseau; Jacques P. Tremblay (Elsevier, 2017)
Laminin-111 protein complex links the extracellular matrix to integrin α7β1 in sarcolemma, thus replacing in dystrophic muscles links normally insured by the dystrophin complex. Laminin-111 injection in mdx mouse stabilized sarcolemma, restored serum creatine kinase to wild-type levels, and protected muscles from exercised-induced damages. These results suggested that increased laminin-111 is a potential therapy for DMD. Laminin subunit beta 1 and laminin subunit gamma 1 are expressed in adult human muscle, but laminin subunit alpha 1 (LAMA1) gene is expressed only during embryogenesis. We thus developed an alternative method to laminin-111 protein repeated administration by inducing expression of the endogenous mouse Lama1 gene. This was done with the CRSPR/Cas9 system, i.e., by targeting the Lama1 promoter with one or several gRNAs and a dCas9 coupled with the VP160 transcription activation domain. Lama1 mRNA (qRT-PCR) and proteins (immunohistochemistry and western blot) were not detected in the control C2C12 myoblasts and in control muscles. However, significant expression was observed in cells transfected and in mouse muscles electroporated with plasmids coding for dCas9-VP160 and a gRNA. Larger synergic increases were observed by using two or three gRNAs. The increased Lama1 expression did not modify the expression of the α7 and β1 integrins. Increased expression of Lama1 by the CRISPR/Cas9 system will have to be further investigated by systemic delivery of the CRISPR/Cas9 components to verify whether this could be a treatment for several myopathies. Keywords: CRISPR/Cas9, laminin-111, dCas9-VP160, Duchenne muscular dystrophy, DMD, transcription factor, transcription, induction of transcription